Cellulose Nanomaterials: Characterization Methods, Isolation Techniques, and Strategies - Bogdan-Marian Tofanica; Aleksandra Mikhailidi; Maria E. Fortună; Răzvan Rotaru; Ovidiu C. Ungureanu; Elena Ungureanu (Crystals)
Nanocellulose, including cellulose nanofibers (CNFs), cellulose nanocrystals (CNCs), and bacterial nanocellulose (BNC), represents a promising class of bio-based nanomaterials derived from natural sources. These materials, derived from plant-based cellulose, are characterized by exceptional mechanical strength, high surface area, biodegradability, and the ability to form stable nanoparticle networks, making them suitable for use in composites, biomedicine, electronics, and many other fields. In this review, we present the latest advancements in the production of nanocellulose, including preparation technologies and methods for chemical and physical modifications to enhance the performance of these materials. We also discuss various applications, such as its use in nanocomposites, sustainable packaging materials, flexible electronic devices, and as a support for biological media. Additionally, the challenges and opportunities related to the scalability of production and their integration into industries with growing economic and ecological demands are explored. The review provides a comprehensive overview of the potential of nanocellulose, highlighting its importance in the context of emerging technologies and sustainability.